PROBLEMS OF INFORMATION AND COMMUNICATION TECHNOLOGIES DURING THE FORMATION OF THE DIGITAL ECONOMY AND SOCIETY - Kniazieva Olena Albertovna; Kuznietsova Olga Viktorovna; Chesnokova Nataliia Vyacheslavovna (Scientific Journal of Pedagogy and Economics, 2021)
Modern society develops under the influence of scientific and technological progress. New relationships in economy, production, education, personal life, new financial instruments and new threats arise. Relevant issues are identifying problems and prospects of development of information and communication technologies (ICT) during the formation of the digital economy and society. The purpose of the article is to systematize the major problems that arise in the development of ICT during the formation of the digital economy and to identify possible consequences of this process. It is proved that introduction of the newest ICT and digital services leads to significant changes in the quantitative and qualitative indicators of the life of the society and are of an institutional nature. Singled out a number of problems during the development of ICT in the digital society, including: digital divide; lack of funds for innovative upgrades; inconsistency of modern education and public administration with the requirements of a new society; shortage of skilled personnel; contradictions between traditional and up-to-date management practices and corruption; activation of cybercrime; the need to create a list of social digital services; international migration of highly skilled personnel. Positive signs in ICT: the continuation of old social and labor activity of citizens; change the semantic content of work towards its intellectualization with the possibility of additional income; increase of ecological economy; creation of new remote jobs; new opportunities for education, tourism, medicine, etc. Systematized negative consequences, namely the growth of cybercrime increasing psychological problems of personality, dependent on ICT networks and energy efficiency, the lack of security of personal space, the need for rapid response to innovative replacement. The proposed measures are aimed at transforming Ukraine into a center of information and communications and digital services for Eastern Europe that can lead to economic breakthrough and overcoming the existing socioeconomic crisis. In further studies are planned to develop a model depending on the pace of digitalization processes of society on the pace of economic development.